O processo de urbanização turística em Natal: a perspectiva do residente - Silva, Karina Messias da (2007)
The objective of the study was to analyze and discuss the process of urbanization in the tourist city of Natal focusing on the actions of the resident agent as a producer of space tourism. The production and expertise in the areas of the city for the performance of tourism have led to the intensification of social problems of nature that comes to few expelling the residents of the beaches. The cut space of the study included the four beaches of Natal / RN, the praias do Centro, Via Costeira, Ponta Negra beach in the Redinha. For this, was conducted a case study, using the technique of questioning, with the application of one hundred and sixteen (116) questionnaires to residents, with age from thirty-five years, between the four of the City Administrative Regions. The results show that the process of urbanization has interferido tourism on the practices of the recreation of residents in the areas as tourism has shown a trend seen in the intensifying problems of social order, such as prostitution, insecurity, pollution of beaches, etc. The combination of these problems are reflected negatively on the tourist areas and are gradually removing the residents. Through this framework problematic, given to tourist areas in the city, the resident still has not positioned the way criticizes the defense of these, choosing not express or adopting a form of discrete event, such as the gradual exit of the areas and electing tourist beaches in other municipalities. The results are of great significance for the direction of a trip planning committed with the participation of the resident in the planning process. The study is to corroborate with the importance of the participation of the resident, before the trip planning, as it is a fundamental agent for the sustainability of space tourism